Conjunctive representation of what and when in monkey hippocampus and lateral prefrontal cortex during an associative memory task. Issue 12 (11th November 2020) - Cruzado, Nathanael A.; Tiganj, Zoran; Brincat, Scott L.; Miller, Earl K.; Howard, Marc W.
Abstract: Adaptive memory requires the organism to form associations that bridge between events separated in time. Many studies show interactions between hippocampus (HPC) and prefrontal cortex (PFC) during formation of such associations. We analyze neural recording from monkey HPC and PFC during a memory task that requires the monkey to associate stimuli separated by about a second in time. After the first stimulus was presented, large numbers of units in both HPC and PFC fired in sequence. Many units fired only when a particular stimulus was presented at a particular time in the past. These results indicate that both HPC and PFC maintain a temporal record of events that could be used to form associations across time. This temporal record of the past is a key component of the temporal coding hypothesis, a hypothesis in psychology that memory not only encodes what happened, but when it happened.